Effects of Artemisia argyi on the antioxidant activity, laying performance and egg quality in laying hens under heat stress - XU Hongrui; CHEN Xiaolian; SHI Jianqing; SONG Qiongli (浙江大学学报. 农业与生命科学版)
Poultry production has been puzzled by the problem of heat stress in laying hens for a long time. Some Chinese herbal medicine had been reported to improve the ability of ant-i heat stress in hens. Artemisia argyi is a kind of abundant resource of herbal medicine in China and was approved clinically to be safe and reliable in human and animals with the property of ant-i inflammation and antioxidation. Few studies have reported the effects of A. argyi on laying hens under heat stress. In order to alleviate the heat-stressed effect and maintain the normal laying performance in laying hens under heat stress by nutrition this study explored the effects of A. argyi on antioxidant activity, laying performance and egg quality in laying hens under heat stress.Seven hundred and twenty Hy-Line Brown layers (38-week-old) were divided into 6 groups with 6 replicates per group and 20 hens per replicate according to the temperature and A. argyi level, including normal temperature (control group) and normal temperature with A. argyi group, high temperature stress group and three A. argyi groups in high temperature. The two control groups were fed with a basal diet. Normal temperature with A. argyi group was fed with basal diet with 3% of A. argyi. High temperature treatments were fed with 1%,2% and 3% of A. argyi, respectively. The preliminary trial period lasted 7 days and trial period lasted 21 days. The antioxidant ingredient and scavenging rates of A. argyi extracts for hydroxide radical, superoxide anion radical and DPPH radical were determined. The laying performance and egg quality were recorded, and the antioxidant indexes and cortisol in serum were determined every 7 days.The results showed that A. argyi has higher antioxidant ingredient and better antioxidant capacity. The contents of flavonoids, total polyphenols, and vitamin C were 87.78 mg/g,126.57 mg/g, and 3.12 mg/g, respectively. The median effective dose of A. argyi extracts for scavenging hydroxide radical, superoxide anion radical and DPPH radical was 356.86 μg/mL, 76.84 μg/mL, 293.67 μg/mL, respectively. There was no significant effect of supplementation of A. argyi on the growth and laying performance in hens under normal condition (P>0.05). Under high temperature, the hens suffered heat stress showed lower daily feed intake, lower laying rate and higher feed to egg ratio. Supplementation of A. argyi in laying hens under heat stress didn’t affect the daily feed intake compared with high temperature stress group (P>0.05), but significantly improved the antioxidant enzyme activity in serum, reduced the content of malondialdehyde and cortisol (P<0.05), increased laying rate, reduced feed to egg ratio (P<0.05), and significantly improved the yolk color and cholesterol levels (P<0.05).The results indicate that A. argyi has good antioxidant effect in vitro and in vivo and can increase the antioxidant activity and improve egg quality through relieving heat stress. According to the effect and cost, the proper supplementation level of A. argyi in laying hens under heat stress is 2%.